Climate Engineering-induced changes in correlations between Earth system variables - Implications for appropriate indicator selection - Nadine Mengis; David P. Keller; Wilfried Rickels; Martin Quaas; Andreas Oschlies (Climatic Change, 2019)
Climate engineering (CE) deployment would alter prevailing relationships between Earth system variables, making indicators and metrics used so far in the climate change-assessment context less appropriate to assess CE measures. Achieving a comprehensive CE assessment requires a systematic and transparent reevaluation of the indicator selection process from Earth system variables. Here we provide a first step towards such a systematic assessment of 10 changes in correlations between Earth system variables following simulated deployment of different CE methods. We therefore analyze changes in the correlation structure of a broad set of Earth system variables for two conventional climate change scenarios without CE and with three idealized CE model experiments: i) Solar Radiation Management, ii) Large-scale Afforestation, and iii) Ocean Alkalinity Enhancement. First, we investigate how the three CE scenarios alter prevailing correlations between Earth system variables when compared to an 15 intermediate-high and a business-as-usual future climate change scenario. Second, we contrast the indicators identified for the non-CE climate change scenarios and the indicators identified when all five scenarios are considered. Finally, we use the identified indicator sets for an evaluation of the five climate change scenarios. We find that the additional indicators provide valuable information for the assessment of the CE measures, and their application hence allows for a more comprehensive and a comparative assessment of the mitigation and CE 20 deployment scenarios.
Keywords: 330; Climate Engineering; Indicator selection; Correlation Changes